507 photo's on the 1988 events (August and September) : demonstrations, strikes against the rejection of the results of the election won by the Nation League for Democracy - Ko Htein Win, (1988)
507 photo's on the 1988 events (August and September) : demonstrations, strikes against the rejection of the results of the election won by the Nation League for Democracy.